2013
DOI: 10.1016/j.bjane.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between doses of intrathecal morphine for analgesia after caesarean

Abstract: Intrathecal morphine 50 μg provides the same quality of analgesia as 100 μg, with a lower incidence of side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
2
12
0
4
Order By: Relevance
“…In the presented study, subarachnoid analgesia was obtained using 0.5% hyperbaric bupivacaine and 0.25% hyperbaric bupivacaine was used for the TAP block. Opioids were not administered into the subarachnoid space due to lack of sufficient postoperative monitoring of the patients and in order to avoid possible complications, such as pruritus and difficulties in passing urine [9,10]. The ultrasound-guided TAP block is a simple and safe analgesic technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented study, subarachnoid analgesia was obtained using 0.5% hyperbaric bupivacaine and 0.25% hyperbaric bupivacaine was used for the TAP block. Opioids were not administered into the subarachnoid space due to lack of sufficient postoperative monitoring of the patients and in order to avoid possible complications, such as pruritus and difficulties in passing urine [9,10]. The ultrasound-guided TAP block is a simple and safe analgesic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Despite small intrathecal doses of morphine provide analgesia after cesarean, more than 59% of patients have moderate-to-severe pain during the first 12 hours after surgery [1][2][3][4]35,36]. In addition, the use of neuraxial opioids has been related to side effects varying in incidence and intensity, according to the dose level [2,3,35,37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of neuraxial opioids has been related to side effects varying in incidence and intensity, according to the dose level [2,3,35,37]. Related to intrathecal opioids, it is essential to find alternatives to improve analgesia and to reduce side effects; 1 option is the combination of local anesthetics with opioids and clonidine because these drugs have synergistic effects [8,[16][17][18][19][20][21][22][23][24][25][26][27]31].…”
Section: Discussionmentioning
confidence: 99%
“…[3] A further lower dose of 50 µg with 100 µg ITM was evaluated in two studies and found to be equally efficacious. [45] These results showed that there is no direct relationship between the dose of ITM and the quality of analgesia. Similar results were demonstrated in previous studies by other investigators.…”
Section: Intrathecal and Epidural Opioidsmentioning
confidence: 96%